A Randomised Controlled Trial Investigating Online Cognitive Behavioural Therapy for Perfectionism to Prevent Eating Disorder Symptoms - Shu, Chloe Yu (Curtin University, 2017)
Clinical perfectionism is a risk factor for eating disorders. The first study confirmed the two-factor structure and validity of the Clinical Perfectionism Questionnaire in female youths. The second study showed that an online cognitive behaviour therapy targeting perfectionism was efficacious in decreasing symptoms of perfectionism, eating disorders, anxiety and depression in female youths. The results support the notion of clinical perfectionism as a transdiagnostic process, and a useful eating disorder prevention target.